Optimization Of Citrate Complex Combustion For Synthesis Of Transition Metal Oxide Nanostructures - Nair, V. M.; Rajan, Jose; Raju, K.; Wariar, P. R. S. (Elsevier Ltd, 2013)

(untitled)
Combustion of citrate complex is a popular choice to synthesize nanocrystals of transition metal oxides in a single-step process. The amount of citric acid used for combustion is conventionally calculated based on the total valence of the oxidizing and reducing agents while keeping the equivalent ratio unity such that combustion energy is a maximum. This paper demonstrates by employing quantum chemical calculations that the amount of citric acid could be reduced to nearly two-third if prepared for appreciable amounts. Transition metal oxides belong to quaternary double perovskite has been synthesized as nanocrystals as examples to validate the calculations.